ANTIOSTEOPOROTIC ACTIVITY OF ANTHRAQUINONE ISOLATED FROM MORINDA CITRIFOLIA FRUITS IN RATS - Joy, Abin; N, Chaitra; M, Ashok; M, Handral (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objectives: This study was designed to investigate the antiosteoporotic activity of isolated anthraquinones from Morinda citrifolia fruit extract in ovariectomy (OVX) induced osteoporotic rats. Methods: All the rats were divided into 4 groups (n=6 each). Group I (sham control) received vehicle, p.o., Group II OVX control (vehicle, p.o.), Group III was OVX+standard raloxifene (5.4 mg/kg, p.o.), and Group IV was OVX+Physcion (100 mg/kg, p.o.) for 90 days. Results: The daily oral administration of isolated compound physcion (100 mg/kg) for 12 weeks to the rats prevented OVX-induced osteoporosis. This was examined by serum biomarkers such as alkaline phosphatase, calcium, and tartrate resistant acid phosphatase and showed significant effects (p<0.0001). The femur bone strength assessed by three-point bending test showed improved bone strength in physcion treated rats, and this was supported by enhanced bone mineral density (p<0.05). The ash parameters of femur bone studied from physcion treated rats exhibited a significant (p<0.0001) value of ash weight followed by ash calcium content. Further, femur bone histological examination revealed the protective effect of the compound physcion (100 mg/kg) against OVX-induced bone loss in rats, where it showed mineralization of trabecular spaces, improved bone compactness thereby intact bone architecture. Conclusion: This study concludes that the isolated anthraquinone physcion had a preventive effect against OVX-induced bone loss in rats. Keywords: Morinda citrifolia, Physcion, Osteoporosis, Bone mineral density, Ash mineral content.